2006
DOI: 10.1038/emm.2006.44
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine suppresses apoptosis and induces neurite outgrowth in PC12 cells through activation of phospholipase D2

Abstract: Lysophosphatidylcholine (LPC) is a bioactive lipid generated by phospholipase A2-mediated hydrolysis of phosphatidylcholine. In the present study, we demonstrate that LPC stimulates phospholipase D2 (PLD2) activity in rat pheochromocytoma PC12 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…It activates multiple molecular targets, including six G protein-coupled receptors, which in turn stimulate various signaling pathways 63,64 . In the present study, we identified that LPC, but not LPA, promoted morphological change in vitro, consistent with a previous report which demonstrated that LPC induces morphological change in PC12 cells by activating phospholipase D 2 65 . Interestingly, the ATX inhibitor BI-2545 also significantly promoted morphological change in BV-2 and SIM-A9 cells, which suggests that LPC may promote morphological change by inhibiting ATX.…”
Section: Discussionsupporting
confidence: 93%
“…It activates multiple molecular targets, including six G protein-coupled receptors, which in turn stimulate various signaling pathways 63,64 . In the present study, we identified that LPC, but not LPA, promoted morphological change in vitro, consistent with a previous report which demonstrated that LPC induces morphological change in PC12 cells by activating phospholipase D 2 65 . Interestingly, the ATX inhibitor BI-2545 also significantly promoted morphological change in BV-2 and SIM-A9 cells, which suggests that LPC may promote morphological change by inhibiting ATX.…”
Section: Discussionsupporting
confidence: 93%
“…2004). Furthermore, a recent study showed that lysophosphatidylcholine promotes neurotrophic effects, such as anti‐apoptosis and neurite outgrowth, through activation of PLD2 (Yun et al. 2006).…”
Section: Discussionmentioning
confidence: 99%
“…2001; Watanabe et al. 2004) and PLD2 enhances lysophosphatidylcholine‐induced neurite outgrowth (Yun et al. 2006).…”
mentioning
confidence: 99%
“…In vivo experiments showed that supplementation of exogenous LPCs could reduce mortality of shock rats and lessen organ damage . The hydrolysis of LPCs has two pathways: one is catalysed by phospholipase D (PLD) to generate PA, and PA can be further metabolized to diacylglycerol and LPA ; in the other pathway, lysophosphatidylcholine is directly converted into LPAs with the action of autotaxin (ATX), which possesses the function of PLD . As phospholipid molecules, LPAs possess diverse biological functions .…”
Section: Discussionmentioning
confidence: 99%